Retrospective Observation of Low-Dose Rituximab Treatment in Chinese Patients With Neuromyelitis Optica Spectrum Disorders in a Real-World Setting - Xiao, Haibing; Zeng, Wenshuang; Li, Ling; Li, Lina; Cui, Yuzhen; Wang, Jie; Ye, Jinhao; Yang, Qingyan (Frontiers in Neurology, 2020)
Objective: To investigate the efficacy and safety of low-dose rituximab (RTX) in the treatment of neuromyelitis optica spectrum disorders (NMOSD) patients. Methods: NMOSD patients were treated with RTX at approximately 25% of the standard dose. The annualized relapse rate (ARR), expanded disability status scale (EDSS) score, visual function system scale (VFSS) and length of spinal cord lesions before and after treatment were statistically compared. Dynamic changes in the proportion of CD19+ B lymphocytes after treatment were monitored, and adverse reactions were recorded. Results: A total of 36 NMOSD patients who received low-dose RTX treatment (375-mg/m2 induction dose and 500 mg every 6 months) were recruited. The average follow-up time after RTX treatment was 19.83 ± 7.74 months. After treatment, the ARR decreased from 1.97 ± 1.93 to 0.12 ± 0.32, the EDSS score decreased from 3.43 ± 1.49 to 3.10 ± 1.88, and the spinal cord lesion length decreased from 5.54 ± 3.96 to 4.31 ± 3.73. These differences were all statistically significant. Subgroup analysis of patients who had previously received nonsteroidal immunosuppressants (NSISs) (n = 20) showed that after RTX treatment, the ARR decreased from 0.66 ± 0.51 to 0.08 ± 0.26, the EDSS score decreased from 3.65 ± 1.22 to 3.40 ± 1.99, and the spinal cord lesion length decreased from 5.68 ± 3.73 to 4.21 ± 3.58. These differences were all statistically significant. VFSS scores did not show a significant change. Kaplan-Meier analysis showed that low-dose RTX significantly delayed recurrence, which was also observed in the subgroup analysis of patients who previously received NSISs. Five relapses in 5 cases were noted after low-dose RTX administration, and the percentage of CD19+ B cells remained <1% in 3 of the cases during the relapses. During RTX treatment and the subsequent follow-up, 8 (22.2%) patients reported adverse reactions, all of which were minor. Conclusion: Low-dose RTX is an effective and safe treatment method for NMOSDs. This method is worth popularizing in developing countries or regions, especially in areas where RTX is not covered by medical insurance.